Increase and changes in distribution of breeding Whooper Swans Cygnus cygnus in northern Sweden from 1972-75 to 1997 - Nilsson, Leif; Andersson, Ove; Gustafsson, Rolf; Svensson, Mikael (Wildfowl, 1998)
In the early decades of the 20th century the Whooper Swan was a rare breeding bird in northen Sweden, estimated at only 20 pairs. After protection from hunting in 1927, the population increased slowly and then more markedly after 1950. A large scale aerial survey was undertaken in 1972-75, when the population of the two northernmost provinces of Sweden (118 000 km^2) was estimated at 310 pairs. In 1997, breeding Whooper Swans were found in all areas between the coast and the mountain chain, whereas the distribution in the 1970s was restricted to some core areas in the north and to scattered pairs. Whooper Swans showed a clear association with wet mires and small lakes. The increase in the population is probably related to increased protection, as well as to better feeding conditions in the agricultural areas in the wintering quarters, thought to have improved the swans' condition at the start of the breeding season.